Caregiving roles perceived effects and coping strategies of older women caregivers - Luan, Bernadethe Marheni (2003)
The social cost of the urbanization and migration of women becomes one of the interesting issues and concern recently. Without regard to the benefits provided to the families, the void of mothers in families forces grandmothers to take over the roles of caring for the children left behind. However, the steady increase of female longevity over their male counterpart connotes the low quality of life during their later age brought about by poverty, widowhood, and deteriorating health. Moreover, in the absence of mothers, the caregiving roles fall more heavily on the older women. Thus, the older women in the community become a high-risk population. The need for understanding the older women cargiver's quality of life and health needs post as a challenge worth exploring. The main purpose of this study was to explore the caregiving roles perceived effects, and the coping strategies of older women in caring for children left behind by overseas Filipino women workers (OFWWs). To answer the stated problems, one-on-one interview and in-depth life stories became the main source of data. Observations during home visits and focus group discussions concretized the phenomenological and research field approaches in exploring sampling methods, particularly network sampling were utilized to identify 20 participants who were between 55 to 84 years of age taking care of grandchildren aged 17 years old and below. The caregiving roles, perceived effects, and coping strategies of older women caregivers were explored and documented during a period of seven weeks of fieldwork.
Camera, cassette recorder, and field notes were used for the data collection with the participants' permission. Four main topics emerged from the study; 1) caregiving, 2) perceived effects, 3) coping strategies, and 4) resiliency. The first topic was subdivided into two sub-topics, roles and history. The caregiving roles consisted of three themes, namely, as guardian mothers, breadwinners, and property watchers. The household, budgeting, religious, decision-making and socio-educational tasks. The caregivers, differences between taking care of one's own children and grandchildren, quality relationship between caregivers, and support availability within family and community. From the second topic on perceived effects emerged three themes in the degree of subjective response: neutral, positive, and negative. From coping strategies topic emerged six themes, praying and faith in God, seeking support behavior and soliciting help from others, problem solving strategies, emotional coping strategies, practicing relaxation, and engaging in productive work. From the last topic on resiliency emerged five themes: meaningfulness and sense of direction and mission, self-efficiency, philosophical attitude in light of sense of morality and faith in God, warm bonding with care-recipient and family members, and community protective factors in light of sense of community involvement experience and positive community norm and feedback. This study showed that the older women's roles in caregiving focused mainly on being guardian mothers, who played a functionally central role in filling the void left by the OFWWs and in saving the life of young generations. Along with their experiences, they subjectively perceived their roles in wide range of degrees relating to the problems encountered and support system availability that could maximally be utilized. They created win-win solutions to their situation in coping with their problems. Their chances to win the situation and solve their problems arising from their caregiving roles came mainly from their personal capacity, courage, flexibility and adaptability to restore balance, with the support from the family and community. Implications drawn from the study emphasized multidimensional aspects including cultural sensitivity and other important aspects in assessing risks population. Enrichment of qualitative research curricula and some additional courses on gerontology and sociology to the recent graduate cirrucula can help the interested researchers to have a broader knowledge and information. Recommendation for further research includes grounded approach to build and develop theories pertaining to perceived effects on caregiving roles, coping and resiliency, health seeking behavior, health belief and practice, and self-promotion among older women caregivers. Ethnographic study on caregiving can also be done to similar population. Further correlational studies may also be conducted to look into some factors that contribute to the perceived effect, coping strategies and resiliency. Community nurse practitioners should focus on primary preventive program in order to optimally assist and sustain older women's capacity, adaptability, and flexibility in taking care of themselves. Likewise, community nurses have the opportunity to develop health promotion programs, utilize family health-center and community based approaches, and actively initiate network, coordination, and collaboration within the community to provide support system through intersectoral and multidisciplinary approaches. Some programs such as catharsis hour program for caregivers and training package modules for caregivers and their families were recommended.
Vita.
Thesis (MA Nursing) -- University of the Philippines, Manila.
Keywords: Caregivers